Pituitary deficiency after aneurysmal subarachnoid hemorrhage (Clinics, 2013)
OBJECTIVE: Aneurysmal subarachnoid hemorrhage puts patients at high risk for the development of pituitary insufficiency. We evaluated the incidence of pituitary dysfunction in these patients and its correlation with clinical outcome. METHODS: Pituitary function was tested in 66 consecutive patients in the first 15 days after aneurysmal subarachnoid hemorrhage. The following were measured in all patients: thyroid-stimulating hormone, free thyroxine, triiodothyronine, luteinizing hormone, follicle-stimulating hormone, total testosterone (in males), estradiol (in females), prolactin, serum cortisol, plasma adrenocorticotropic hormone, growth hormone and insulin growth factor. RESULTS: The endocrine assessment was made at a mean of 7.4 days (standard deviation ±6.6) after subarachnoid hemorrhage. Forty-four (66.7%) female and 22 (33.3%) male patients were evaluated. Thirty-nine patients (59.1%) had some type of pituitary dysfunction. Follicle-stimulating hormone/luteinizing hormone deficiency was the most frequent disorder (34.8%), followed by growth hormone/insulin growth factor (28.7%), adrenocorticotropic hormone (18.1%) and thyroid-stimulating hormone (9%). Seventeen (25.7%) patients showed deficiencies in more than one axis. A greater incidence of hormone deficiency was observed in patients with a Glasgow Coma Scale score ≤13 (t test, p = 0.008), Hunt-Hess grade ≥4 (t test, p;0.05) with increased hospitalization or clinical outcome. CONCLUSION: Pituitary dysfunction was identified in a substantial portion of patients with previous aneurysmal subarachnoid hemorrhage, but no association was found between this dysfunction and poor clinical outcome.